DIGITALISASI PENDIDIKAN HUKUM DAN PROSPEKNYA PASCA PANDEMI COVID-19 - Dian Rachmat Gumelar; Sri Sophiarani Dinnur (Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2020)
This writing aims to describe the situation of digitizing legal education and its prospects during the Covid-19 pandemic. This paper aims to explain how the digitization of legal education can work in accordance with the era of the industrial revolution 4.0 and in the midst of the Covid-19 pandemic. The method used in this paper is the literature method, which relies on the use of reference books as study material to describe the theoretical framework as well as the limited space for movement during large-scale social restrictions. Utilization of the internet in education is not new. Many in various countries have used digitalization in education. However, in Indonesia before the pandemic its utilization was not optimal. The dependence of the community on the internet makes digitalization of education the only solution so that learning activities can still be carried out during the Covid-19 pandemic like this. There are facilities and infrastructure constraints that must be met in order to support learning activities. This writing was made to better understand the definition of digitalization of education, life in the era of the industrial revolution 4.0, the obstacles and challenges faced in this education digitization system, as well as the readiness of academic facilities and infrastructure in supporting the digitization of legal education.Penulisan ini bertujuan untuk mendeskripsikan situasi digitalisasi pendidikan hukum dan prosepeknya pada masa pandemi covid-19 ini. Tulisan ini bertujuan untuk menjelaskan bagaimana digitalisasi pendidikan hukum ini dapat berjalan sesuai dengan era revolusi industri 4.0 dan di tengah pandemi covid-19. Metode yang digunakan dalam penulisan ini adalah metode kepustakaan, yakni bertumpu kepada penggunaan referensi pustaka sebagai bahan kajian untuk menggambarkan kerangka teoritisnya seriring terbatasnya ruang gerak pada masa pembatasan sosial berskala besar. Pendayagunaan internet dalam pendidikan bukanlah hal yang baru. Banyak di berbagai negara sudah menggunakan digitalisasi dalam pendidikan. Hanya saja, di Indonesia pada masa sebelum pandemi pendayagunaanya belum optimal. Ketergantungan masyarakat pada internet membuat digitalisasi pendidikan ini menjadi satu-satunya solusi agar kegiatan pembelajaran tetap dapat dilaksanakan dimasa pandemi covid-19 seperti ini. Adapun kendala sarana dan prasarana yang harus dipenuhi dalam rangka menunjang kegiatan pembelajaran. Penulisan ini dibuat untuk lebih memahami kembali definisi dari digitalisasi pendidikan, kehidupan pada era revolusi industri 4.0, hambatan dan tantangan yang dihadapi dalam sistem digitalisasi pendidikan ini, serta kesiapan sarana dan prasarana akademik dalam mendukung digitalisasi pendidikan hukum.